Effectiveness of educational videos and booklets on stunting prevention knowledge among prospective newlyweds - Adhe Lisna; Asri Hidayat; Dewi Rokhanawati (Journal of Health Technology Assessment in Midwifery, 2026)
Background of Study: Stunting remains a significant public health concern in Indonesia, necessitating preventive interventions that commence in the preconception period. Adequate knowledge among prospective brides and grooms is expected to influence health-related behaviors, particularly in improving nutritional status before pregnancy, which plays a critical role in maternal health, fetal growth, and pregnancy outcomes. Therefore, stunting prevention initiated during the preconception period through increasing the knowledge of prospective couples is a key strategy, including the utilization of educational media such as videos and booklets.Objective of Study: The objective of this study was to compare the effectiveness of educational videos and booklets in improving stunting prevention knowledge among prospective brides and grooms attending the Offices of Religious Affairs (KUA) in five districts, Manado City.Method: This study employed a quantitative research design with a quasi-experimental approach. The population consisted of all prospective brides attending the Offices of Religious Affairs (KUA) in the districts of Mapanget, Singkil, Tuminting, Bunaken, and Paal Dua, Manado City. Purposive sampling was used to select the participants, with a total of 20 respondents assigned to the video group and 20 respondents to the booklet group. Data analysis was carried out using paired sample t-tests and independent sample t-tests.Results: The video group showed higher post-test scores (19.50 ± 1.85) than the booklet group (17.85 ± 2.18) (p = 0.014). ANCOVA indicated an effect of educational media on post-test knowledge (p = 0.025).Conclusion: Video-based education is more effective than booklet-based education in improving prospective brides’ knowledge of stunting prevention.